Design of Learning Media for Audacity-Assisted Doppler Effect Practicum Tools - Desy Widaningrum (Universitas Padjadjaran, 2021)
The Doppler effect is one of the important materials in studying the sound of a still or moving object. The purpose of this study is to develop learning media in the form of Doppler effect practicum tools assisted with audacity. The research method used is Research and Development (R & D). The product produced in this study is a Doppler Effect practicum tool in the form of a source car and a listener car equipped with a speed controller as a speed controller and a speaker as a sound source, a trajectory as long as 3 meter, as well as assisting with audacity on a personal computer or laptop. The audacity-assisted hearing frequency measurement tool was tested by varying the speed of the source car and the direction of the source car, the approaching and farther away from the listener's car. The results of the measuremen of this tools are in accordance with theoretical calculations, having a difference of 0.81 Hz at a speed of 0.33 m/s, a difference of 3.05 at a speed of 0.38 m/s, and a difference of 3.88 at a speed of 0.44 m/s. The relative accuracy of the measurement results to the comparative theoretical value by calculation is 99.9%. Based on the results of this study, it can be concluded that the learning media in the form of Doppler effect practicum tools assisted by audacity that were designed can be applied in physics learning.Keywords: audacity, Doppler effect, practicum tools.